Genome Identification and Expression Analysis of GRAS Family Related to Development, Hormone and Pathogen Stress in Brachypodium distachyon - Tang, Zejun; Song, Na; Peng, Weiye; Yang, Yang; Qiu, Tian; Huang, Chenting; Dai, Liangying; Wang, Bing (Frontiers in Sustainable Food Systems, 2021)
GRAS transcription factors are widely present in the plant kingdom and play important roles in regulating multiple plant physiological processes. Brachypodium distachyon is a model for grasses for researching plant-pathogen interactions. However, little is known about the BdGRAS family genes involved in plant response to biotic stress. In this study, we identified 63 genes of the GRAS family in B. distachyon. The phylogenetic analysis showed that BdGRAS genes were divided into ten subfamilies and unevenly distributed on five chromosomes. qRT-PCR results showed that the BdGRAS family genes were involved in the growth and development of B. distachyon. Moreover, the expression of the HAM subfamily genes of BdGRAS changed during the interaction between B. distachyon and Magnaporthe oryzae. Interestingly, BdGRAS31 in the HAM subfamily was regulated by miR171 after inoculation with M. oryzae. These results provide insight into the potential functions of the BdGRAS family in disease resistance.